(untitled) (Bioagro, 2026)
The growing demand for healthy fruits is driving the development of sustainable technologies to ensure food safety. In this context, the application of organic amendments represents a viable alternative for soils low in organic matter. It was evaluated the effect of three doses of vermicompost (0, 90, 180 g·planta-1) y humic substances (0, 50, y 100 g·planta-1) on yield, fruit quality, and soil properties of strawberry (cv. San Andreas) production. A randomized complete block design with a 3×3 factorial arrangement was used. The combination of 180 g·planta-1 of vermicompost y 50 g/plant of humic substances resulted in the highest yield (216.68 g·planta-1), with 90% of the fruits classified as extra quality. Regarding soil quality, the organic matter content total nitrogen, y cation exchange capacity, increased. It has been demonstrated that the combined or individual application of organic inputs enhances the productivity y sustainability of strawberry cultivation in soils low in organic matter.